Development of a complex multidisciplinary medication review and deprescribing intervention in primary care for older people living with frailty and polypharmacy - Eloise Radcliffe; Alejandra Recio Saucedo; Clare Howard; Claire Sheikh; Katherine Bradbury; Paul Rutter; Sue Latter; Mark Lown; Lawrence Brad; Simon D.S. Fraser; Kinda Ibrahim (PLoS ONE, 2025)
Introduction Reducing polypharmacy and overprescribing in older people living with frailty is challenging. Evidence suggests that this could be facilitated by structured medication review (SMR) and deprescribing processes involving the multidisciplinary team (MDT). This study aimed to develop an MDT SMR and deprescribing intervention in primary care for older people living with frailty. Methods Intervention development was informed by the Medical Research Council framework for complex intervention and behaviour change and implementation theories. Intervention planning included: 1) a realist review of 28 papers that identified 33 context-mechanism-outcome configurations for successful MDT SMR and deprescribing in primary care, 2) a qualitative study with 26 healthcare professionals (HCPs), 13 older people with polypharmacy and their informal carers. The intervention’s guiding principles were developed and intervention functions proposed, discussed and refined through an iterative process in four online co-design stakeholder workshops. Results The final version of the complex intervention consisted of five components: 1) Proactive identification of patients living with frailty and polypharmacy for targeted SMR using routinely collected primary care data; 2) HCPs’ preparation using an evidence-based deprescribing tool to identify and prioritise high-risk medications for deprescribing; 3) Preparing patients and carers using a leaflet sent prior to SMR explaining the purpose of SMR and reasons for potentially stopping or changing medications; 4) Conducting a person-centred SMR face-to-face or by phone, tailored to patient/carer needs, involving other MDT members based on their expertise; 5) Tailored follow-up plans allowing continuity of care and highlighting signs and symptoms for patients and carers to monitor, and arranging follow-up through text, phone or face-to-face appointment. Conclusion A complex MDT SMR and deprescribing intervention for older people living with frailty was developed to address multiple challenges to deprescribing. The use of rigorous methods and behaviour and implementation theories potentially maximises the intervention’s feasibility, acceptability and successful implementation.